"There Is So Much More for Us to Lose If We Were to Kill Ourselves": Understanding Paradoxically Low Rates of Self-Harm in a Socioeconomically Disadvantaged Community in London. (January 2021) - Polling, Catherine; Woodhead, Charlotte; Harwood, Hannah; Hotopf, Matthew; Hatch, Stephani L.
London has unexpectedly low overall rates of self-harm in public health data and contains highly deprived areas with these paradoxically low rates. Qualitative data were collected via interviews and focus groups with 26 individuals living and working in one such area. Using the Stress Process Model, we explore why this ethnically diverse community, which is exposed to multiple, chronic stressors, might nonetheless appear to have low rates of self-harm. Participants described significant impacts of stressors on the mental health of people locally. These were partly buffered by social resources related to community solidarity and a culture of self-reliance. However, identifying oneself as mentally ill through being known to have self-harmed was seen as highly risky, diminishing a person's social status and exposing them to additional stressors from the community and services. Consequently, people tended to hide distress, respond with behaviors less linked to mental illness, and avoid mental health services.